Dynamic phosphorus expert system with QoS support algorithms - Shuminoski, Tomislav; Naumoski, Andreja; Naumoski, Zdravko; Janevski, Toni; Mitreski, Kosta (My University, 2009)
In this paper we present conceptual model for ecological management system with data acquisition module, combine with telecommunication-routing algorithms for data processing which help to deliver the data to processing station; fast and accurate. Then as a part of this system, the data will be used to build mathematical model for the total phosphorus concentration for short-term period. The total phosphorus (TP) component plays an important role in the functioning of aquatic ecosystem, affecting the whole food web chain that this element is participating. This is why; the protection of the lake must be direction in controlling this kind of ecological hazards. In our case study of the Lake Prespa we used data collected for 16 months period using old style-techniques, we build mathematical model of the total phosphorus component. Presented conceptual system starts with data acquisition with wireless sensors networks using advanced routing algorithms with high-level of QoS provisioning. Later the data is inputted into the model to give reliable information about the ecological status of the lake ecosystem for short period. After the processing the results are available to the decision-maker and environmental management engineers. In future we plan to develop more precision ecological models and telecommunication modules and combine with GIS techniques for better spatial view of the ecosystem.
Keywords: Lake Prespa, QoS routing algorithm, Phosphorus concentration